Ensuring human rights in the context of digital technologies during an armed conflict - Stepanenko, Nataliia; Perepadin, Kostiantyn; Степаненко, Наталія В'ячеславівна; Перепадін, Костянтин Вікторович (ТОВ "Наукова установа "Правові горизонти", 2025)
In the context of the full-scale armed conflict caused by the russian federation’s aggression against Ukraine, digital technologies have become an integral part of both hostilities and the daily lives of the civilian population. This poses unprecedented challenges for ensuring and protecting human rights. The article analyzes the key issues arising at the intersection of digital technologies, human rights, and armed conflict in the Ukrainian context. It examines the use of digital platforms for spreading disinformation and propaganda, which violates the right to receive reliable information, as well as countermeasures against these phenomena and the associated risks of restricting f reedom of speech. Threats to the right to privacy and personal data protection, stemming f rom increased state surveillance and data collection under martial law, are analyzed, emphasizing the importance of adhering to the principles of legality and data minimization. The impact of cyberattacks on critical inf rastructure as a factor violating the socio-economic rights of the civilian population and the complexity of legally qualifying such actions are highlighted. Simultaneously, the positive potential of digital technologies as a tool for documenting war crimes and human rights violations using open-source intelligence (OSINT), photo, and video evidence is demonstrated, underscoring the importance of adhering to standards for handling digital evidence (e.g., the Berkeley Protocol). The article is based on the analysis of current research by Ukrainian academic institutions, human rights, and expert organizations. It concludes that a comprehensive approach is necessary, including improving national legislation and international legal norms, strengthening cybersecurity, developing standards for working with digital evidence, and ensuring a balance between national security needs and the protection of fundamental human rights and f reedoms in wartime
Keywords: human rights; digital technologies; martial law; armed conflict; disinformation